2009
DOI: 10.1093/ejechocard/jen214
|View full text |Cite
|
Sign up to set email alerts
|

Role of real-time three-dimensional transoesophageal echocardiography for guiding transcatheter patent foramen ovale closure

Abstract: Patent foramen ovale (PFO) is a relatively common congenital condition which has been implicated in cryptogenic stroke as a result of paradoxical thromboembolism by right-to-left shunting. Many studies have demonstrated that transcatheter PFO closure significantly reduced the incidence of recurrent strokes in a small group of high-risk patients with PFO and atrial septal aneurysm compared with antithrombotic drugs. Two-dimensional transoesophageal echocardiography (2D TEE) has become the election technique for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…3). More recent reports have continued to investigate the utility of RT3DTEE for closure of ASDs [13][14][15][16] as well as expand on the usefulness and additive value of RT3DTEE with other interventional procedures. Saric et al [17 ] recently reported on a series of 706 RT3DTEE studies, including 23 with ASDs, and the development of a standardized three-dimensional protocol for evaluating and displaying the interatrial septum.…”
Section: Real-time Three-dimensional Transesophageal Echocardiographymentioning
confidence: 99%
“…3). More recent reports have continued to investigate the utility of RT3DTEE for closure of ASDs [13][14][15][16] as well as expand on the usefulness and additive value of RT3DTEE with other interventional procedures. Saric et al [17 ] recently reported on a series of 706 RT3DTEE studies, including 23 with ASDs, and the development of a standardized three-dimensional protocol for evaluating and displaying the interatrial septum.…”
Section: Real-time Three-dimensional Transesophageal Echocardiographymentioning
confidence: 99%
“…The recent development of 3D fully sampled matrix array TEE transducers has allowed real-time acquisition and on-line display of 3D images, while providing superb imaging of specific cardiac structures including the interatrial septum [14,15]. Several studies demonstrated the clinical utility of real-time 3DTEE for the guidance of device closure of atrial septal defects and patent foramen ovale [16][17][18][19][20]. Thus, the aim of this study was (1) to quantify the dynamic changes of ASD size and shape using real-time 3DTEE, (2) to compare realtime 3DTEE and standard 2DTEE methods for measuring defect size and rim length, and (3) to investigate the ability of 3D to measure the maximal diameter of the ASD defect versus the deployed maximal device diameter in patients who subsequently underwent percutaneous transcatheter closure of the ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complicated morphology of multiple ASDs, importance of real-time 3D TEE during this procedure should be highlighted. Recently, several studies have proved the advantage of real-time 3D TEE and realized the invaluable role of this new method in preoperative assessment, intraoperative guidance, as well as postoperative evaluation during intervention procedure [16][17][18][19]. Successful closure of ASD is dependent on accurate assessment of ASD size, rim architecture, and relationship of the defect to adjacent cardiac structures.…”
Section: Discussionmentioning
confidence: 99%